Supporting Victimized Children in Iran's Legislative Criminal Policy - Kazemi, Seyyed Sajjad; Sobhani, Neda (Jurnal Cita Hukum, 2021)
In today's society, children have a special place and it is no longer the case that the child is considered a family property rather, the child is an individual with his or her personality and social status and the rights that society has for him/her. But what matters is whether the rights in our society are sufficient for children and just by telling them can it stabilize the child's position within society and save him from any attack? What should be accepted without question is that the answer is no. Because children need special rights and special protections because of their age and physical and intellectual weakness and if there is no executive guarantee to protect them, of course, not only will these rights not be respected, but they will also be violated and children who are more vulnerable than others suffer a lot. What this research specifically focuses on, a comprehensive review of child and adolescent protection law whereas, following the international obligations our country has committed to and adhered to in compliance with the convention on the rights of the child in 2000, it was approved by the Islamic Consultative Assembly in 2003. The author's attempt has been to under the pretext of reviewing and evaluating the aforementioned law, evading the existing penal regulations regarding the protection of children and adolescents in the Iranian penal system and thereby evaluate the weaknesses of the aforementioned laws and thus help the legislator to develop and enforce laws protecting certain vulnerable groups such as children.Keywords: Differential criminal policy; children; child abuse; victimization   Mendukung Anak-Anak Korban Dalam Kebijakan Kriminal Legislatif Iran AbstrakDalam masyarakat sekarang ini, anak memiliki tempat khusus dan tidak lagi dianggap sebagai milik keluarga. Anak adalah individu dengan kepribadian dan status sosialnya tersendiri, serta memiliki hak-hak yang sama sebagaimana masyarakat pada umumnya. Tetapi yang terpenting adalah apakah hak-hak dalam masyarakat kita sudah cukup untuk melindungi anak-anak, dan hanya dengan memberi tahu mereka kemudian dapatkah hal itu menstabilkan posisi anak dalam masyarakat dan menyelamatkannya dari kejahatana apa pun? Pastinya, anak-anak membutuhkan hak dan perlindungan khusus, karena usia dan kelemahan fisik dan intelektual mereka. Jika tidak ada jaminan eksekutif untuk melindungi mereka, maka tentu saja hak-hak ini tidak hanya tidak dihormati, tetapi juga akan dilanggar. Fokus penelitian ini adalah tinjauan komprehensif terhadap undang-undang perlindungan anak dan remaja. Karena sesuai dengan kewajiban internasional, negara Iran telah berkomitmen dan taat menjalankan konvensi tentang hak-hak anak tahun 2000, dan telah disetujui oleh Majelis Permusyawaratan Islam Iran pada tahun 2003.Upaya penulis adalah berupaya meninjau dan mengevaluasi undang-undang tersebut, serta menghindari peraturan pidana yang ada mengenai perlindungan anak dan remaja dalam sistem pidana Iran, serta mengevaluasi kelemahan hukum yang disebutkan dan  membantu legislator untuk mengembangkan dan menegakkan hukum yang melindungi kelompok rentan tertentu seperti anak-anak.Kata kunci: Kebijakan pidana diferensial, anak, penganiayaan anak, viktimisasi Поддержка Пострадавших Детей В Законодательной Уголовной Политике В Иране АннотацияДети играют особую роль в сегодняшней культуре и больше не считаются семейной собственностью. Дети - это люди со своими личностными качествами и социальным положением, и они имеют те же привилегии, что и остальное общество. Но самый важный вопрос - адекватны ли права нашего общества, чтобы защитить их, и может ли закон стабилизировать статус ребенка в обществе и спасти его от какого-то преступления? Детям, конечно же, нужны особые привилегии в силу возраста, физической и интеллектуальной слабости. Если исполнительные органы не обещают защищать их, эти меры защиты не только будут отвергнуты, но и будут использоваться для злоупотреблений. Целью данного исследования является тщательное изучение законодательства, касающегося безопасности детей и подростков. Поскольку иранское государство согласилось  принять Конвенцию о правах ребенка в 2000 году, а в 2003 году она была принята Исламской консультативной ассамблеей Ирана в соответствии с международными обязательствами. Автор пытается изучить и оценить эти правила, а также обойти действующее уголовное законодательство о безопасности детей и подростков в иранской уголовной системе, также оценить недостатки перечисленных законов и помочь законодателям в разработке и применении законов, которые смогли бы защищать маргинализированные группы, такие как дети.Ключевые слова: Дифференцированная Уголовная Политика, Дети, Жестокое Обращение С Детьми, Виктимизация.